Pendekatan Kuantitatif dalam Pembedahan Bunga: Penggunaan Rumus untuk Mengukur Simetri dan Struktur Bunga - Moch. Naufal Ramdhani; Hanifah Flora Reine; Labibah Fatihatu Hanin; Ingrie Laila; Mutia Ramadhina Hastin; Ita Fitriyyah (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
This research examines quantitative approaches in flower dissection, with a focus on measuring symmetry and flower structure using mathematical formulas. This research aims to develop an objective method for analyzing flower morphology to support taxonomic, evolutionary and ecological studies of plants. Data was collected through morphometric measurements on various flower species with radial and bilateral symmetry characters. Parameters measured include petal length, corolla width, spreading angle, and number of reproductive parts. The analysis was carried out using geometric formulas to calculate the symmetry index and proportions of the flower structure. The research results show that flowers with radial symmetry have a higher symmetry index value than flowers with bilateral symmetry. Additionally, variations in flower structure were found to correlate with ecological adaptations, such as pollination strategies by insects or wind. This approach successfully revealed consistent mathematical patterns in floral design, providing new insights into the relationship between structure and biological function. This study shows that quantitative approaches can increase precision in the analysis of flower morphology, while providing a new tool for exploring the evolutionary dynamics of plants. This method can be applied to cross-disciplinary research involving morphology, genetics and plant ecology.